Semiotics in Mass Marriage Traditions in the Community of Serdang Village Toboali District Sout Bangka Belitung Island - Anggun Sukmarani; Yenny Puspita; Juaidah Agustina (Edumaspul: Jurnal Pendidikan, 2024)
This research was carried out with the aim of knowing and describing the semiotics in the mass marriage tradition of the people of Serdang Village, Toboali District, South Bangka Regency, Bangka Belitung Islands. The method used by researchers in this research is a qualitative descriptive method using Roland Bhartes' semiotic analysis to discuss the meaning of denotation, connotation and myth. Researchers conducted an analysis of the symbols and meanings contained in the mass marriage tradition. This research uses primary data sources and secondary data sources. The data collection techniques used in the research are observation techniques, interview techniques, recording techniques and documentation techniques. The data analysis technique used in the research is descriptive qualitative. The results of the research that has been carried out show that this mass marriage tradition was carried out by parents in 1935 and is still carried out today. In ancient times, this tradition was held after harvesting the garden with the aim of being a form of gratitude and helping the economy. in carrying out the wedding. Over time, this tradition is carried out with the aim of enlivening, preserving and maintaining the culture that has been passed down from generation to generation so that it is known to the outside community and does not become extinct. From the results of this research, researchers obtained nine symbols and two rituals which have denotational and connotative meanings in the mass marriage process. Keywords : Semiotics, Mass Marriage Traditions ABSTRAKPenelitian ini dilakukan bertujuan untuk mengetahui dan medsekripsikan semiotik dalam tradisi kawin massal masyarakat Desa Serdang Kecamatan Toboali Kabupaten Bangka Selatan Kepulauan Bangka Belitung. Metode yang digunakan peneliti dalam penelitian ini yaitu metode desakriptif kualitatif dengan menggunakan analisis semiotika Roland Bhartes membahas mengenai makna denotasi, konotasi dan mitos. Peneliti melakukan analisis terhadap simbol dan makna yang terdapat dalam tradisi kawin massal. Dalam penelitian ini menggunakan sumber data primer dan sumber data sekunder. Teknik pengumpulan data yang digunakan dalam penelitian yaitu menggunakan teknik observasi, teknik wawancara, teknik rekam dan teknik dokumentasi. Teknik analisis data yang digunakan dalam penelitian yaitu secara deskriptif kualitatif. Hasil penelitian yang telah dilakukan, tradisi kawin massal ini sudah dilaksanakan oleh orang tua dahulu pada pada tahun 1935 dan masih tetap dilakukan hingga saat ini, tradisi ini pada zaman dahulu di adakan pada saat setelah memanen hasil kebun yang bertujuan sebagai bentuk rasa syukur dan membantu perekonomian dalam melaksanakan pernikahan. Dengan seiring zaman tradisi ini dilakukan bertujuan untuk memeriahkan, melestarikan dan menjaga budaya yang turun temurun agar dikenal masyarakat luar dan tidak punah. Dari hasil penelitian ini, peneliti mendapatkan sembilan simbol dan dua ritual yang memiliki makna denotasi dan konotasi dalam proses kawin massal. Kata Kunci: Semiotik, Tradisi Kawin Massal